Theoretical Evaluation of a Bulky Ortho-Thioalkyl-Azobenzene as an Alternative to Photocontrol Structural Cytotoxic Effects of Metal-Free and Disulfide Oxidized hsod1 in Pathogenesis of Als - Aspee-Lamas, A (Royal Society of Chemistry, 2025)
This study presents a novel photopharmacological strategy to mitigate the cytotoxic effects of apo-hSOD1S-S, a misfolded protein implicated in neurodegenerative diseases. Using quantum chemical calculations and molecular dynamics simulations, we demonstrate that ortho-thio-substituted azobenzene photoswitches (ortho-TABPs) can be employed to precisely modulate the dynamics of the crucial electrostatic loop (EL) in apo-hSOD1S-S. We establish that larger ortho-S-alkyl substituents on the ortho-TABP enhance its redox stability, favouring the cis conformation through the modulation of the position of the n → π* transition. This stability is crucial for operation within the reducing cellular environment. Furthermore, we demonstrate the successful and consistent photomodulation of EL conformational dynamics in apo-hSOD1S-S through covalent tethering of an ortho-TABP. This control is achieved by leveraging the thermodynamically stable trans conformation of the photoswitch, which allosterically influences the EL and consequently, the geometry of the Zn-binding site, a critical determinant of apo-hSOD1S-S cytotoxicity. This work paves the way for developing targeted therapies for neurodegenerative diseases by demonstrating the precise and effective photomodulation of apo-hSOD1S-Svia rationally designed ortho-TABPs. © 2025 The Royal Society of Chemistry.